Creating a learning organization : promoting excellence through education - Braham, Barbara J. (Crisp Pub. Menlo ParkUS, 1995)
Defines a learning organization and shows why learning is important both to the individual and to the organization's success. Includes topics such as: determining the type(s) of learning needed by the organization; stages of individual learning ; and, barriers to organizational learning.